Drivers of illicit alcohol consumption among at-risk populations aged 15–29 years old in Zambia: a qualitative perspective - Matenga, Tulani Francis L.; Zyambo, Cosmas; Phiri, Masauso Moses; Zulu, Richard; Mukupa, Musawa; Mabanti, Kumbulani; Hainze, Anna; Menda, Dhally M.; Rizzo, Angela; Ogwell, Ahmed; Goma, Fastone M.; Achoki, Tom (Frontiers in Public Health, 2025)
BackgroundIllicit alcohol consumption is a major public health problem in Zambia and many other countries in Sub-Saharan Africa. This study aimed to determine drivers of illicit alcohol consumption among at-risk populations, such as youths, in selected urban areas in Zambia, using the social-ecological model as a lens to understand these drivers.MethodsThrough a qualitative approach, we conducted semi-structured interviews with 12 key stakeholders from the Ministry of Health, Zambia Revenue Authority, local council public health departments, and rehabilitation centers. We also interviewed 30 alcohol consumers who frequent alcohol retail settings such as bars or liquor stores. Participants were purposively selected based on their knowledge of illicit alcohol consumption.ResultsSocial demographic factors such as age and sex were identified as key drivers. Adolescents as young as 10 years old initiated illicit consumption, with males constituting the majority of consumers. Limited job opportunities and recreational facilities in communities encouraged young people to consume illicit alcohol; this is worsened by the availability of alcohol in their social circles. Peer influence was also found to be a major driver of illicit alcohol consumption, as cultural norms normalized alcohol use. Lack of productive activities and economic disparities were also found to drive consumption among this group. Low-income individuals sought cheaper alternatives, such as home-distilled spirits or fermented alcohol, due to their affordability and availability in disadvantaged neighbourhoods. Social norms, such as the consumption of homemade alcoholic beverages during social gatherings such as weddings, were also significant drivers.ConclusionDespite policies and state agencies banning illicit alcohol sale and production, the sale of alcoholic beverages to young people and weak enforcement of regulations across the country, especially in urban areas increases young people’s risk of consuming illicit alcohol. Applying the social-ecological model emphasizes the need for multi-level interventions. These interventions should target individuals, communities, and policy levels. Specifically, they should aim to regulate alcohol consumption, disrupt the social environments that promote illicit alcohol consumption, and ultimately facilitate positive behavior change among young people.